Spiritual Development Across The Curriculum In Educational Systems - ghasempoor, ali (Advances in Social Sciences Research Journal, 2017)
This paper looking back over the last several years and asserts that the spiritual is rooted in the essence of being human and shows how spirituality is related to a search for a deeper philosophical meaning of life. Human beings search for meaning, purpose and direction in life and spiritual development is inextricably linked with this process Spiritual development in this sense must be holistic. The spiritual dimension of education must engage the body, mind and heart. Spiritual development implies change, with a progression from immaturity towards maturity, from the simple to the complex, from the superficial to the profound. In relation to this the writer discusses what spiritual education should involve and the contribution different aspects of the curriculum can make.